A Newly Described, Highly Prevalent Arterial Pedicle Perfuses Both Gracilis and Profunda Artery Perforator Flap Tissues: An Angiographic Study of the Medial Thigh - Hammond, Jacob B.; Flug, Jonathan A.; Foley, Brittany M.; Bryant, Lyndsey A.; Casey, William J., III; Velazco, Cristine S.; Rebecca, Alanna M. (Journal of Reconstructive Microsurgery, 2020)
Background Novel secondary flap options are paramount for patients who are not candidates for common reconstructive methods. The purpose of this study is to identify the prevalence of single arterial pedicle supplying both the gracilis muscle and medial thigh tissue carried in a profunda artery perforator (PAP) flap. Such a pedicle could allow the creation of a chimeric gracilis and PAP flap with a single-arterial anastomosis.Methods We conducted a retrospective review of 157 lower extremity computed tomography (CT) angiograms to assess the vasculature of the thigh soft tissues. Imaging evaluation was supervised by a board-certified musculoskeletal radiologist.Results Prevalence of a single-arterial pedicle to a gracilis and PAP flap in each patient was 59% (31% within the right leg and 28% in the left leg). Furthermore, 16% of patients had a common arterial pedicle in both lower extremities.Conclusion Existence of a single-arterial pedicle to both the gracilis muscle and PAP flap tissues is frequently present in most patients in at least one lower extremity. This chimeric flap configuration could serve as a reconstructive avenue for patients, particularly those who have exhausted other more common flap options. Screening angiography is warranted in patients looking for this anatomic variation to establish its presence.
Keywords: microsurgery; thigh; pedicle